Kesan Interaksi di Antara Program Latihan Berdasarkan Analisa Keperluan Latihan Dengan Motivasi Terhadap Prestasi Kerja - Muhammad Ramlie, Hassan Shaari (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Training literature has show that needs analysis may affect individual attitudes and behaviors. The effect of needs analysis issues on job performance does not clear if motivation is present in organization. This study used qualitative and quantitative research designs as a procedure for collecting and analyzing the data. The outcomes of multiple regression analysis showed that motivation played a moderating role in the relationship between needs analysis and job performance. These findings are consistent with training literature. This study has significant implications to theory, research methodology and human resources practitioners. In term of theoretical contribution, these findings showed that worker motivation played important rolls that can influence the training management. Meanwhile, this study also used to support human resource manager to design the training programmed that can influence the employee 's attitude and behavior then their job performance